Resonant tunnelling between the chiral Landau states of twisted graphene lattices - Greenaway, M.T.; Vdovin, Evgeny E.; Mishchenko, A.; Makarovsky, Oleg; Patanè, Amalia; Wallbank, J.R.; Cao, Y.; Kretinin, A.V.; Zhu, M.J.; Morozov, S.V.; Fal’ko, V.I.; Novoselov, K.S.; et al. (Nature Publishing Group, 2015)
A class of multilayered functional materials has recently emerged in which the component atomic layers are held together by weak van der Waals forces that preserve the structural integrity and physical properties of each layer. An exemplar of such a structure is a transistor device in which relativistic Dirac Fermions can resonantly tunnel through a boron nitride barrier, a few atomic layers thick, sandwiched between two graphene electrodes. An applied magnetic field quantises graphene's gapless conduction and valence band states into discrete Landau levels, allowing us to resolve individual inter-Landau level transitions and thereby demonstrate that the energy, momentum and chiral properties of the electrons are conserved in the tunnelling process. We also demonstrate that the change in the semiclassical cyclotron trajectories, following an inter-layer tunnelling event, is analogous to the case of intra-layer Klein tunnelling.